Relationship between social capital and access or use of health services by adults: a systematic review - Luiza Foltran de Azevedo Koch; Paula Porto Spada; Bruna de Souza Romano; Juliana Schaia Rocha; Ádelin Olívia Lopes Joly Rodrigues; Marcos Pascoal Patussi; Letícia Maíra Wambier; Flares Baratto-Filho; Marilisa Carneiro Leão Gabardo (Revista Sul-Brasileira de Odontologia, 2025)
The search for health services is influenced by a number of factors. One such factor is social capital, which can be conceptualized as a network of social relationships that can provide individuals and groups with access to resources and support. Objective: The aim of this systematic review was to explore the relationship between social capital and access or use of health services by adults. Material and methods: Studies were searched in PubMed, Scopus, Web of Science, Lilacs, BBO, Cochrane, and in the gray literature. The quality of the studies was analyzed using the Downs and Black checklist. Results: Of the 4815 studies that were evaluated, 14 met the eligibility criteria and were included. Six studies were classified as low risk of bias, six were moderate, and two were high. While social capital seems to be associated with access or use of health services by adults, it was not possible to carry out a meta-analysis to prove these findings, due to the heterogeneity of studies. Conclusion: It was not possible to confirm the association investigated here, then it becomes clear the need for a standardization in the design of future studies that will allow comparisons.